Literasi Moderasi Beragama dalam Perspektif Pendidikan Agama Kristen - Esti Regina Boiliu (Institut Agama Kristen Negeri Toraja, 2022)
Religious tolerance education as a strategy for preventing conflicts in a multicultural society. Instilling Christian ideals like peace and mutual love is a crucial job of Christian religious education. This essay was written with the intention of examining how Christian Religious Education views religious literacy by forbidding instruction on how to live in love and promote peace among others. This article was written using a qualitative method and a literature review approach. The author looked at earlier works and discovered that there are still few studies on joint moderation literacy from the perspective of Christian religious education. Even if it is understood, Christian Religious Education is a field where many people receive helpful instruction in applying Christian values, which are fully described in Galatians 5:22–23, to living their lives in the larger community. As a result, the findings of this study offer positive values, instructing people on how to live in peace, accept other people's viewpoints, love one another, and coexist.